A framework for earthquake resilience at neighborhood level. Issue 4 (13th April 2020) - Aslani, Fereshteh; Amini Hosseini, Kambod; Fallahi, Alireza
Abstract : Purpose: Despite long decades of research studies in the field of urban neighborhood resilience, there are still some unknown dimensions. In this regard, the study aims to develop a new framework for assessment of physical and social resilience at neighborhood level against earthquake. Design/methodology/approach: Accordingly, first all indicators affecting earthquake resilience at neighborhood level have been determined. Subsequently, they have been weighted and prioritized, using analytical hierarchy process technique. One of the neighborhoods of Tehran city in Iran was selected for the case study. Then, four criteria of "robustness, " "redundancy, " "rapidity" and "resourcefulness" were considered as the basis for assessing neighborhood resilience. Findings: It is shown that besides four well-known criteria, four other criteria including "adaptability, " "regularity, " "density" and "efficiency" should also be considered to assess earthquake resilience at neighborhood level. Therefore, a new framework is developed and formulated at this level. Paying attention to all eight criteria, the appropriate interventions to improve resiliency can be addressed. Practical implications: This study proposes several practical approaches toward the more resilient neighborhoods against earthquakes. By considering the complexity and dynamic characteristics of earthquake resilience, it recommends the implementation of all resilience phases at every neighborhood to increase resilience. Originality/value: This study proposes a framework in which in addition to physical and tangible indicators of resilience, non-physical and intangible ones are presented. Also, it is shown that besides well-known criteria, other criteria should also be considered using practical and community-based approaches.